The therapeutic potential of escitalopram in the treatment of panic disorder - Mark H Townsend (Dove Medical Press, 2007)
Mark H Townsend, Erich J ConradDepartment of Psychiatry, Louisiana State University Health Sciences Center New Orleans, New Orleans, Louisiana, USAAbstract: Panic disorder is a chronic and disabling condition that is often accompanied by other psychiatric and medical conditions. The serotonin reuptake inhibitors (SSRIs) and serotoninnorepinephrine reuptake inhibitors (SNRIs) have been used effectively with panic disorder (PD) and conditions in which panic attacks frequently occur. Escitalopram is the most selective SSRI and a variety of evidence suggests it is of great value in the treatment of panic disorder. In this paper, we review the theoretical and practical implications of its use.Keywords: panic disorder, escitalopram, antidepressant, serotonin